The New Method of Multidimensional Sequence Structure Snalysis and Its Implementation in STATISTICA System. - Manasyan, A. (Mathematical Problems of Computer Science, 2021)
The article presents DSA software, which works in STATISTICA environment and implements the method of multidimensional sequence structure analysis. The method was described in [1]. The new tool can be used in teaching purposes as well for real data analysis.